Validity of the Peer Tutor Guide: Innovation Service Guidance Counseling Based on 4D Model in Bullying Prevention - Putu Ari Dharmayanti; Kadek Suranata; Luh Putu Sri Lestari; Suci Nora Julina Putri (Program Studi Bimbingan dan Konseling Universitas PGRI Semarang, 2025)
Abstract. This study developed and validated a peer-tutoring service guide to prevent bullying in elementary schools. Peer tutoring was chosen because classmates strongly shape attitudes and behavior. Using the 4D model (Define, Design, Develop, Disseminate), the study engaged five experts in guidance and education and three elementary teachers. The guide was produced through needs analysis and design workshops, then evaluated by experts. Content validity was excellent, with a Content Validity Index (CVI) of 1, indicating strong appropriateness for school use. A pilot with 30 students showed a significant decline in bullying, based on pre-test and post-test comparisons. These results suggest the guide effectively supports teachers and students in preventing and addressing bullying. The study recommends broader implementation across schools, accompanied by training and ongoing evaluation, to strengthen prevention efforts and foster safe, inclusive school climates. Collaboration with parents and the wider community is essential to sustain and amplify impact over time.